2021
DOI: 10.1108/medar-12-2020-1123
|View full text |Cite
|
Sign up to set email alerts
|

Fostering performance management in healthcare: insights into the role of big data

Abstract: Purpose This study aims to understand how Big Data foster a greater acceptance of performance management systems (PMS) discourses in health care. Design/methodology/approach This paper focusses on the case of head and neck cancer treatment and prevention and benefits from the analysis of archival sources and 19 interviews with physicians in the field. It uses the framework of the Middle Range theory (MRT) to understand whether, in the case of head and neck cancer, Big Data may favour the enactment of PMS dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…To accelerate digitalization, hospitals must invest in technology to automate processes and streamline operations, moving in two distinct directions: focusing on the organizational level (moving from episodic to coordinated care), where telemedicine is prioritized, and introducing digital solutions to enable new models of care (progressing toward personalized care and increasing the focus on prevention and wellness) [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To accelerate digitalization, hospitals must invest in technology to automate processes and streamline operations, moving in two distinct directions: focusing on the organizational level (moving from episodic to coordinated care), where telemedicine is prioritized, and introducing digital solutions to enable new models of care (progressing toward personalized care and increasing the focus on prevention and wellness) [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…The optimal use of resources has a critically important role for healthcare operators in assessing the quality of the healthcare service provided and also requires appropriate technologies to ensure the rational use of resources [107][108][109]. Benzidia et al (2021) claim that extracting new insights from existing volumes of structured and unstructured data related to medical treatments and products improves decision-making and enables a better understanding of each patient's costs [93,110].…”
Section: Big Data and Digital Transformationmentioning
confidence: 99%
“…Tus, the development of smart healthcare has become an important and widely followed research issue. In recent years, with the development of big data technology, many hospitals have been mining and analyzing medical big data through big data-related technologies, laying the foundation for further building smart hospitals [2][3][4]. It has also been confrmed that the medical application of big data technology plays an important role in safeguarding human lives [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the implementation of digital technologies are becoming increasingly relevant for corporate and performance management (Oliver, 2018;Marrone and Hazelton, 2019;Wang et al, 2020aWang et al, , 2020bChatterjee et al, 2021;Jun et al, 2021), and especially ETs have demonstrated in the last years to be particularly supportive in fostering these issues in health care (Spanò and Ginesti, 2021), transportation (Chhabra et al, 2021), manufacturing (Rezaei et al, 2017) and so on.…”
Section: Introductionmentioning
confidence: 99%